PENGEMBANGAN MEDIA POP UP BOOK PELAJARAN IPAS MATERI METAMORFOSIS, PERUBAHAN BENTUK MAKHLUK HIDUP - Al Frostasya, Ghiska; Kartono, Kartono; Pranata, Rio (Universitas Tanjungpura, 2024)
This research aims to produce Pop Up Book-Based Learning Media for Science and Science Learning Material on Metamorphosis, Changes in the Shape of Living Creatures for Class III of 36 Pontianak City Public Elementary Schools which has been tested for validity and practic for use. The research method used is Research and Development (R D). The development stages used in this research adopted the ADDIE (Analysis, Design, Development, Implementation and Evaluation) development model developed by Dick Carry. The results of research on the development of learning media are learning media based on the results of analysis for class III students, namely media that is interesting, both in terms of appearance and media content. Based on the results of the expert validator's assessment, the Pop Up Book media was declared